Trial watch: Dendritic cell-based anticancer therapy - Bloy, Norma; Pol, Jonathan; Aranda, Fernando; Eggermont, Alexander; Cremer, Isabelle; Fridman, Wolf Hervé; Fučíková, Jitka; Galon, Jérôme; Tartour, Eric; Spisek, Radek; Dhodapkar, Madhav V; Zitvogel, Laurence; et al. (Oncoimmunology, 2014)
The use of patient-derived dendritic cells (DCs) as a means to elicit therapeutically relevant immune responses in cancer patients has been extensively investigated throughout the past decade. In this context, DCs are generally expanded, exposed to autologous tumor cell lysates or loaded with specific tumor-associated antigens (TAAs), and then reintroduced into patients, often in combination with one or more immunostimulatory agents. As an alternative, TAAs are targeted to DCs in vivo by means of monoclonal antibodies, carbohydrate moieties or viral vectors specific for DC receptors. All these approaches have been shown to (re)activate tumor-specific immune responses in mice, often mediating robust therapeutic effects. In 2010, the first DC-based preparation (sipuleucel-T, also known as Provenge®) has been approved by the US Food and Drug Administration (FDA) for use in humans. Reflecting the central position occupied by DCs in the regulation of immunological tolerance and adaptive immunity, the interest in harnessing them for the development of novel immunotherapeutic anticancer regimens remains high. Here, we summarize recent advances in the preclinical and clinical development of DC-based anticancer therapeutics.
Keywords: Toll-like receptor agonists; MUC1, mucin 1; antigen cross-presentation; DC, dendritic cell; mDC, mature DC; DC-based vaccination; TLR, Toll-like receptor; MRC1, mannose receptor, C type 1; pDC, plasmacytoid DC; autophagy; Treg, regulatory T cell; regulatory T cells; WT1, Wilms tumor 1; immunogenic cell death; FDA, Food and Drug Administration; IFN, interferon; TAA, tumor-associated antigen; iDC, immature DC